2019
DOI: 10.1007/s13595-019-0798-y
|View full text |Cite
|
Sign up to set email alerts
|

Fine root morphology and growth in response to nitrogen addition through drip fertigation in a Populus × euramericana “Guariento” plantation over multiple years

Abstract: & Key message Nitrogen addition through drip fertigation to a poplar plantation (Populus × euramericana BGuariento^) promoted fine root growth only in the early period. The relationship between root growth and soil N content was positive in the first 2 years, but became negative in the third year when the soil N availability had substantially increased. & Context Nitrogen (N) deficiency is common in forest soils, and N addition is sometimes applied in the case of intensive plantations. There is a need to bette… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 63 publications
2
8
0
Order By: Relevance
“…These results suggested that soil N availability and root N uptake played important roles in the root growth of P. tabuliformis, which made roots absorb more resources and directly changed the plant biomass allocation pattern (Davis et al 2000). Despite directly inhibiting the R/S ratio, N addition could indirectly increase it through increasing SNC and RNC, same as other studies (Yan et al 2019). As for F. chinensis, on the one hand, N could indirectly increase R/S ratio through its positive effects on RNC and SNC, similar to P. tabuliformis.…”
Section: Effect Of N Deposition On Tree Functional Traitssupporting
confidence: 74%
“…These results suggested that soil N availability and root N uptake played important roles in the root growth of P. tabuliformis, which made roots absorb more resources and directly changed the plant biomass allocation pattern (Davis et al 2000). Despite directly inhibiting the R/S ratio, N addition could indirectly increase it through increasing SNC and RNC, same as other studies (Yan et al 2019). As for F. chinensis, on the one hand, N could indirectly increase R/S ratio through its positive effects on RNC and SNC, similar to P. tabuliformis.…”
Section: Effect Of N Deposition On Tree Functional Traitssupporting
confidence: 74%
“…However, the deeper soil layers contain leached nutrients (Fig. 1), which suppress the growth of fine roots 30 . Furthermore, surface soil layers are affected first when N is added, the foraging response of fine roots then leads to a change the fine roots in surface layer, which mediates the vertical fine root distribution 40 .…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have found that the effects of N deposition are greater on lower order roots than on higher order roots 9,29 . Other studies have shown that the biomass of fine roots in the upper soil layers is significantly higher than that in other soil layers 15 and that N addition significantly increases the SRL and SRA of fine roots in the upper soil layer (0-30 cm) 30 . However, Yan et al 31 demonstrated that N addition reduced the SRA of fine roots.…”
mentioning
confidence: 83%
“…In drought studies, root development was dependent on soil saturation (Carthy et al, 2018), and lateral root growth was inhibited by PEG exposure, which may be controlled by the PtabZIP1-like (Dash et al, 2017) and PtaJAZ3 and PtaRAP2.6 (Dash et al, 2017(Dash et al, , 2018 genes. Root biomass density, length, surface area, and SRL were also stimulated by N fertilization (Yan et al, 2019), and SRL and fine:coarse root ratio were strongly influenced by the form of N used (Domenicano et al, 2011;Yan et al, 2019), reflecting the plasticity of root architectural traits in Populus. Understanding the genes and networks underlying root architectural change to the environment will allow for future selection for stress resistance.…”
Section: 8mentioning
confidence: 99%